Importance of feedlot in pasture management systems for the Brazilian semi-arid region - Alves, Francisco Gleyson da Silveira; Silva, Shirlenne Ferreira; Alves, Sávio Levy Sousa; Ferreira, Francisca Débora da Silva; Lopes, Alexsandro Ferreira; Silva, Amanda Monteiro da; Edvan, Ricardo Loiola (Revista de Ciências Agroveterinárias, 2025)
In the semi-arid region's ecosystem, animal production is influenced by spatial and interannual variation in forage supply, both in quantitative and qualitative terms. Knowledge of the effect of animal trampling on vegetation and soil attributes is crucial for an improvement animal production. Understanding how the physical attributes of soils and forage plants respond to intense grazing pressures can explain the main causes of degradation in natural pastures, especially when grazing occurs during the dry season of the year. Animal trampling induces changes in these attributes and in plants, particularly when the stocking rate is not respected and when it occurs at a time when the plant-soil system is weakened, leading to soil compaction. Seasonality in forage production imposes severe restrictions on forage supply and nutrient availability in production systems. Feed shortages during the dry season are one of the main problems producers faces. Therefore, pasture management strategies in semi-arid regions must be adopted to maintain animal production during this period, without harming the forage plant and soil.